Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1600-6143.2006.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dialysis and Older Age on Survival after Liver Transplantation

Abstract: Because creatinine is heavily weighed in the MELD (model for end-stage liver disease) score, we sought to determine the impact of MELD-based organ allocation on outcomes after transplantation in the preand post-MELD eras, focusing on recipients over age 65 on dialysis prior to transplant. A total of 20 196 patients from the UNOS database were analyzed. Comparing the pre-MELD to MELD era, there was a 41% increase in patients on dialysis (p < 0.0001), and a 117% increase in combined liver/kidney transplants (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 22 publications
0
27
1
2
Order By: Relevance
“…Although data regarding insurance status collected in the NCDB has not been independently validated, it is highly complete and is abstracted from hospital records, in which billing data are likely to be accurately recorded. In addition, there were important patient characteristics that we were unable to consider, such as HCV serostatus, 19 HBV antigen positivity, 20 a-fetoprotein level, 21 diabetes status, 22 or dialysis requirement before LT. 23 We also had no available data concerning whether individual patients were referred to an LT program. It has been suggested that racial/ethnic differences in referral to a LT center may be one of the most important factors underlying the disparity in access to LT for minority patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although data regarding insurance status collected in the NCDB has not been independently validated, it is highly complete and is abstracted from hospital records, in which billing data are likely to be accurately recorded. In addition, there were important patient characteristics that we were unable to consider, such as HCV serostatus, 19 HBV antigen positivity, 20 a-fetoprotein level, 21 diabetes status, 22 or dialysis requirement before LT. 23 We also had no available data concerning whether individual patients were referred to an LT program. It has been suggested that racial/ethnic differences in referral to a LT center may be one of the most important factors underlying the disparity in access to LT for minority patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous investigations have suggested that renal dysfunction is associated with a prolonged hospital and intensive care unit stay, more postoperative infections, and poor survival rates. 13,14 Dellon and associates 15 have suggested that combined liver and kidney transplant may be the best treatment for older patients who need preoperative renal replacement therapy. The liver transplant procedure is difficult and is associated with major hemodynamic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Abb. 6; [8]). SALT und ähnliche Modelle müssen daher weiter entwickelt und prospektiv evaluiert werden.…”
Section: > Die Herausforderung Ist Die Erfolgswahrscheinlichkeit Einunclassified